Change: modulation and modularity. For a musical semiosis - Smith, Simon (Revista Acta Semiotica, 2025)
This article gives a musical inflection to Landowski’s socio-semiotics. Starting from the premise that the regimes of interaction model (like the semiotic square itself) is not a classificatory grid but a dynamic model of situated social practices that traverse and combine semiotic styles, I imagine its two typical sensemaking pathways — one articulated around manipulation, the other around adjustment — as respectively narrative and musical semioses, which we can contrast on four axes : the way they span action cycles, their orientation towards goals or resonance with atmospheres, their logic of change and their timing principles. A musical semiosis means both a modular configuration of ongoingness (modules playing in parallel, fading up or down at moments of transition) and a modulating configuration of ongoingness (a perception of any “problem” as a modulating pattern with a cyclical rhythm, which our “solution” needs to adjust to). Given a musical inflection, a semiotics of sentient experience is also a semiotics of repeat performance, where feelings and expectations of change presentify as we move on, through modified repetitions, criss-crossing parallel tracks.